2013
DOI: 10.4143/crt.2013.45.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Which Patients Might Benefit from Postmastectomy Radiotherapy in Breast Cancer Patients with T1-2 Tumor and 1-3 Axillary Lymph Nodes Metastasis?

Abstract: PurposeThis study compared the clinical outcomes of T1-2N1 breast cancer patients with and without postmastectomy radiotherapy (PMRT). Risk factors for loco-regional recurrence (LRR) were identified in order to define a subgroup of patients who might benefit from PMRT.Materials and MethodsOf 110 T1-2N1 breast cancer patients who underwent mastectomy from January 1994 through December 2009, 32 patients underwent PMRT and 78 patients did not. Treatment outcomes and risk factors for LRR were analyzed.ResultsThe 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…location, HER2̸neu overexpression and negative oestrogen receptor status were associated with poorer outcomes and a reduction in OS (4)(5)(6)10,12). Higher-grade disease, a triple-negative subtype, age <40 years, HER2̸neu overexpression and negative oestrogen receptor status were all identified as independent poor prognostic factors for LRR (5,6,10,12,13). In order to fully elucidate the effect of these factors, and other factors, such as the use of systemic therapy, on the suggested LRR rates and OS when PMRT is used, future prospective randomised trials are warranted.…”
Section: Test a Resultsmentioning
confidence: 99%
“…location, HER2̸neu overexpression and negative oestrogen receptor status were associated with poorer outcomes and a reduction in OS (4)(5)(6)10,12). Higher-grade disease, a triple-negative subtype, age <40 years, HER2̸neu overexpression and negative oestrogen receptor status were all identified as independent poor prognostic factors for LRR (5,6,10,12,13). In order to fully elucidate the effect of these factors, and other factors, such as the use of systemic therapy, on the suggested LRR rates and OS when PMRT is used, future prospective randomised trials are warranted.…”
Section: Test a Resultsmentioning
confidence: 99%
“… 21 , 22 Adequate radiation or hormonal therapy was performed as indicated. 23 , 24 The radiological response was evaluated using breast MRI for the primary breast lesion and chest CT for the lymph node lesions with RECIST criteria 1.0. 25 Pathologic complete response (pCR) was defined as complete disappearance of invasive carcinoma in both breast and axillary lymph nodes after three cycles of chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…For example, although young age was a common risk factor, the cutoff for young age varied among the studies [ 7 9 , 13 ]. Moreover, in several studies including ours, age was not associated with an increased risk of LRR after mastectomy [ 11 , 12 , 14 , 26 ]. In our study, HER2 overexpression was identified as an independent risk factor for LRR.…”
Section: Discussionmentioning
confidence: 54%